2019
DOI: 10.5817/sp2019-2-3
|View full text |Cite
|
Sign up to set email alerts
|

Career Adaptability of Vocational Education and Training Graduates in the Period of Prospective School-to-Work Transition

Abstract: The completion of vocational education and training (VET) and the subsequent school-to-work transition are important steps on the career pathway. The school-to-work transition is a long-term process with unclear boundaries involving a number of potentially difficult aspects. Psychological resources for successful schoolto-work transitions are reflected in the multidimensional psychosocial construct of career adaptability. The goal of the present study was to examine the role of selected demographic and school-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 66 publications
(107 reference statements)
0
11
0
Order By: Relevance
“…Guan et al, 2017), self-esteem (van Vianen, Klehe, Koen, & Dries, 2012), career decision self-efficacy (Douglas & Duffy, 2015), and vocational identity (Negru-Subtirica et al, 2015) have been found to positively predict career adaptability. Furthermore, education (Zacher, 2014), training (Hlad′o, Lazarová, & Hloušková, 2019; Koen et al, 2012), academic achievement (Negru-Subtirica & Pop, 2016), work volition (Autin, Douglass, Duffy, England, & Allan, 2017), and career calling (Praskova, Hood, & Creed, 2014) have been identified as significant predictors of career adaptability. Career adaptability is not only influenced by factors within the individual, but it is also positively associated with factors connected with social background, more specifically, career adaptability has been found to be positively associated with perceived social support, particularly with parental support, perceived teacher or school support, and peer support (Ebenehi, Rashid, & Bakar, 2016; Ginevra, Nota, & Ferrari, 2015; Y.…”
Section: The Construct Of Career Adaptabilitymentioning
confidence: 99%
“…Guan et al, 2017), self-esteem (van Vianen, Klehe, Koen, & Dries, 2012), career decision self-efficacy (Douglas & Duffy, 2015), and vocational identity (Negru-Subtirica et al, 2015) have been found to positively predict career adaptability. Furthermore, education (Zacher, 2014), training (Hlad′o, Lazarová, & Hloušková, 2019; Koen et al, 2012), academic achievement (Negru-Subtirica & Pop, 2016), work volition (Autin, Douglass, Duffy, England, & Allan, 2017), and career calling (Praskova, Hood, & Creed, 2014) have been identified as significant predictors of career adaptability. Career adaptability is not only influenced by factors within the individual, but it is also positively associated with factors connected with social background, more specifically, career adaptability has been found to be positively associated with perceived social support, particularly with parental support, perceived teacher or school support, and peer support (Ebenehi, Rashid, & Bakar, 2016; Ginevra, Nota, & Ferrari, 2015; Y.…”
Section: The Construct Of Career Adaptabilitymentioning
confidence: 99%
“…Graduates who have obtained only an apprenticeship certificate are not permitted to enroll in university and non-university tertiary education. Therefore, many vocational graduates do not pursue tertiary education but seek to enter employment directly upon graduation (Hlad'o et al, 2019). Specifically, approximately two-thirds of graduates with a vocational education apprenticeship and more than one-third of graduates with a school graduation certificate enter the labor market after graduation (Chamoutová et al, 2019).…”
Section: Present Study Contextmentioning
confidence: 99%
“…In this line of thinking, it would be useful to design training in various career adaptability activities, such as exploring possible career selves and career options, making plans and decisions to pursue chosen career options, and developing tactics to overcome possible career obstacles to promote career adaptability resources (Rossier, 2015). A previous study on Czech vocational graduates showed that using career guidance services positively predicted career adaptability (Hlad’o et al, 2019). As such, we would like to encourage the use of career counseling services in vocational graduates who are about to make their career transitions and advocate its focus on career adaptability.…”
Section: Career Adaptability Career Decision-making Self-efficacy And...mentioning
confidence: 99%
“…An individual's capacity to adjust to a change in job is what is meant by the term "career adaptability," which was used by (Duffy et al, 2015). In addition, Hlado et al (2019) state that when a problem arises at work, individuals may become increasingly interested in their future career. This interest may manifest itself in a variety of ways, including taking charge of their training or self-reflection, investigating prospects, and researching the many potential future scenarios.…”
Section: Career Adaptabilitymentioning
confidence: 99%